Theoretical approaches to low energy K̅N interactions - Cieplý Aleš; Mai Maxim (EPJ Web of Conferences, 2016)
We provide a direct comparison of modern theoretical approaches based on the SU(3) chiral dynamics and describing the low energy K̄N data. The model predictions for the K̅N amplitudes and pole content of the models are discussed.